Influence of Heat Treatment and Dispersing Agent Addition on Hydroxyapatite Powder Properties and its Suspension Characteristics - Ahmed, Y.M.Z.; El-Sheikh, S.M.; Zaki, Z.I. (Asian Journal of Chemistry, 2015)
Colloidal processing route is considered as a potential way of successfully fabricating a homogeneous and complex shape ceramic body. In this regards, preparation of a well dispersed ceramic suspension is a vital in deciding the suitability of applying this processing route for ceramic green body fabrication. Controlling the physical properties of hydroxyapatite powder through the calcination process would enhance the particle properties in terms of particle size, its distribution and surface area. It was found that hydroxyapatite powder calcined at 1100 °C possesses physical and chemical properties suitable for colloidal processing route. Also the utilizing of calcined powder at 1100 °C with 0.3 wt. % sodium polyacrylate dispersant proved to be beneficial in producing a low viscosity and high turbidity suspensions.